Issues Concerning the Relationship between Accounting and Taxation in Determining Financial Result - Moisescu, Florentina (European Journal of Sustainable Development, 2018)
The tax result does not reflect the real financial performance of a company but rather shows a result of taxation which is to determine the size of tax for a company. Therefore, in Romanian accounting there are a lot of different ways which are used to obtain an `embellished` accounting result due to a large variety of accounting policies and methods which allows the company to choose the desired outcome. In our county, the main goal of an enterprise seems to be either the decrease of the financial result in order to avoid payment of a bigger tax to the state tax authority or the postponement of it, while companies from other countries want a financial result as big as possible so that they can attract investors. Keywords: financial outcome, accounting, fiscality, accountig policy, revenue, cost, tax